2010
DOI: 10.1016/j.ydbio.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Severe developmental bone phenotype in ClC-7 deficient mice

Abstract: Bone development is dependent on the functionality of three essential cell types: chondrocytes, osteoclasts and osteoblasts. If any of these cell types is dysfunctional, a developmental bone phenotype can result. The bone disease osteopetrosis is caused by osteoclast dysfunction or impaired osteoclastogenesis, leading to increased bone mass. In ClC-7 deficient mice, which display severe osteopetrosis, the osteoclast malfunction is due to abrogated acidification of the resorption lacuna. This study sought to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Along the same line, data from in vitro experiments show that allowing osteoclasts to resorb bone facilitates bone formation by osteoblasts in the resorbed areas (82,83). Furthermore, studies indicate that osteoclasts deposit TRACP on the bone surface leading to recruitment of osteoblasts (84), a finding that correlates with the high levels of TRACP found on the resorbed bone surfaces in ADO patients and other acid secretion-deficient systems (41,85,86) (Fig. 3).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 76%
See 1 more Smart Citation
“…Along the same line, data from in vitro experiments show that allowing osteoclasts to resorb bone facilitates bone formation by osteoblasts in the resorbed areas (82,83). Furthermore, studies indicate that osteoclasts deposit TRACP on the bone surface leading to recruitment of osteoblasts (84), a finding that correlates with the high levels of TRACP found on the resorbed bone surfaces in ADO patients and other acid secretion-deficient systems (41,85,86) (Fig. 3).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 76%
“…Studies in the aged ovariectomized rat model using these inhibitors have shown that bone resorption is lowered, while osteoclast numbers and bone formation are maintained (63,73), thereby mimicking the phenotype of the ADO patients and ClC-7-deficient mice (11,41,85,86). Treatment with these inhibitors also resulted in increased BMD and bone strength (63,73), thereby underlining the potential of these molecules.…”
Section: Clc-7 Inhibitorsmentioning
confidence: 94%
“…Loss of function of CLCN7 and TCIRG1 -genes that encode key components of the osteoclast acid-secreting machinery -leads to complete abrogation of bone resorption in both humans and mice, in spite of increased osteoclast number; this condition, therefore, is termed osteoclast-rich osteopetrosis (61). Nevertheless, both humans and mice with osteoclast-rich osteopetrosis have increased bone formation (62)(63)(64). In contrast, loss-of-function mutations of RANK lead to complete absence of osteoclasts and "osteoclast-poor" osteopetrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased bone strength has been observed in cortical, but not vertebral bone, of cathepsin K deficient mice [53], and in cortical bone of Ae2 a,b deficient mice [54]. However, these mice also have thickened cortices, as opposed to acid secretion deficient mice, which have very little if any normal cortex [25]. Furthermore, the Ae2 a,b and cathepsin K deficient mice also show less dramatic accumulation of calcified cartilage in the bone marrow cavities [54;55].…”
Section: Discussionmentioning
confidence: 99%